Antioxidants and Cardiovascular Disease - Bourassa, Martial G.; Bourassa, Martial G.; Tardif, Jean-Claude.; Tardif, Jean-Claude. (Developments in Cardiovascular Medicine, 2006)
Antioxidants and Cardiovascular Disease, Second Edition addresses a complex but very timely and fascinating problem in cardiovascular medicine. It is written by recognized experts in the fields of atherosclerosis and antioxidants. It should be of interest not only to academicians but also to practicing physicians. The first five chapters review the general concepts of oxidative stress and their relationship to lipid metabolism, endothelial dysfunction, genetics and transcriptional factors. The next seven chapters describe recently defined markers of oxidative stress, pharmacological compounds with antioxidant activity, natural antioxidants found in micronutrients and in nutrient-rich diets, and reviews the recent evidence for their efficacy or lack of efficacy in patients with cardiovascular disease or cardiovascular risk factors. The last seven chapters discuss the potential therapeutic benefits of antioxidants in a number of cardiovascular conditions which include atherosclerosis, restenosis after percutaneous coronary intervention, major cardiovascular risk factors such as hypertension, diabetes mellitus and dyslipidemia, and left ventricular dysfunction and congestive heart failure. Martial G. Bourassa, M.D. and Jean-Claude Tardif, M.D. are affiliated with the Montreal Heart Institute, Research Center and Department of Medicine, Faculty of Medicine, University of Montreal, Montreal, Quebec, Canada.